AN INVESTIGATION OF ANXIETY OF THAI TEACHING IN CHINESE UNIVERSITIES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Foreign language study has been increasingly important, as well as study of Thailanguage and culture by Chinese people which is getting more and more popular everyyear. The purpose of this research was to study anxiety problems and solutions of Thaiteachers that experienced in preparing to teach Thai language in Chinese Universities.This research is a case study limited to 6 of Thai teachers from Chiang Mai University,Chiang Mai, Thailand, purposefully selected to conduct the individual interview processwhich was followed by the qualitative method. The In-depth interviews wereundertaken with a range of teachers in Year 2018 to 2019. The data was analyzedmanually by using Content Analysis after the data collection over. Both experiencedteachers and non-experienced teachers felt anxious as the same which different factorscome into play. Mostly, there are lots of negative feelings but anxiety experiences couldbe the driving force that made these teachers prepares more before going on to be Thaiteachers in Chinese universities. It was not a bad experience only but was a verymemorable once in a life time one for this teacher to share and guide future teachers